PENGARUH CITRA TOKO DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN ULANG MELALUI KEPUASAN PELANGGAN (STUDI PADA KONSUMEN TOKO GUNUNG AGUNG CIREBON MALL) - Aliyan, Muhammad Ivan; Farida, Naili; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2015)
This research was conducted in account of the vastly developing book industries, indicated by an increasing number of competitors in the market. Specifically this research was focused on Toko Gunung Agung in Cirebon Mall, which was a part of one of the biggest network in Indonesia's book industry, However in the period 2011-2013 there is a gap between expectations and reality of customers who conduct transactions student book. Therefore the company had to recreate the store's positive image and raise the service quality standard in order to ensure the customer's satisfaction which will lead to a re-purchase decision.                The purpose of this research was to describe the effect of store image and service quality to repurchase decision through customer satisfaction Toko Gunung Agung Cirebon Mall customer. This research was of explanatory type, with the means of questionnaire and interview for data obtained. Sampling was carried through purposive sampling, in the number of 100 from the respective store customers. Data was then analyzed through appropriate qualitative and quantitative analysis techniques, in which the quantitative techniques include validity test, reliability test, correlation coefficient, single and multiple regression, coefficient of determination, significance test ( t and F test), and path analysis.                The result showed that store image (X1)) and service quality (X2) simultaneously as well as partially affected customer satisfaction (Y1) and repurchase decision (Y2)). Furthermore, path analysis showed that the direct effect of store image (X1)) and service quality (X2) on repurchase decision (Y2) was significantly bigger than its indirect effect through customer satisfaction (Y1).                Finally, it was suggested that Toko Gunung Agung Cirebon Mall should improve the arrangement of their product's display, exterior design of the store, adding the number of computer which used as catalog, adjusting the store music properly, and to held a discount program once in a while in order to survive the increasing competition in the industry.